2016
DOI: 10.1186/s40780-016-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

Validated determination method of tramadol and its desmethylates in human plasma using an isocratic LC-MS/MS and its clinical application to patients with cancer pain or non-cancer pain

Abstract: BackgroundThis study aimed to develop a simultaneous determination method for tramadol and its desmethylates in human plasma using isocratic liquid chromatography coupled to tandem mass spectrometry and to validate it for pharmacokinetic evaluation in patients with cancer pain or non-cancer pain.MethodsThe pretreatments for human plasma involved protein precipitation using acetonitrile and methanol under basic conditions. Tramadol, O-desmethylate, N-desmethylate, and N,O-didesmethylate were separated on an oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Trough concentrations at steady state at median oral daily doses of 112.5 mg divided into three doses (Tanaka et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Trough concentrations at steady state at median oral daily doses of 112.5 mg divided into three doses (Tanaka et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, we decided to use “large experimental animal models” to observe extensive whole-body pharmacokinetics in a context comparable to patient physiology [ 15 , 16 ]. In our study, we also evaluated M1, the main TR metabolite, levels and its PK parameters since it has about 300-fold higher affinity for the μ receptor than TR [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tramadol (TR) is an opioid analgesic widely used to treat moderate, severe, and chronic pain, such as oncologic and postoperatory pain [ 1 , 2 ]. It acts as an opioid μ 1 receptor agonist and monoamine reuptake inhibitor and as a target for some protein coupled receptor and ligand-gated ion channels [ 3 , 4 ]. The common adverse effects of tramadol are somnolence, seizures, nausea, and vomiting [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey revealed that several methods have been reported for the determination of TRM either alone or in the presence of other co‐formulated materials. These include spectrophotometric (Abdellatef, ; Amin, Adawy, Ali, & El‐Shahatt, ; Dhumal, Bhusari, Ghante, & Jain, ; Glavanović, Glavanović, & Tomišić, ; Lakshmi, Ravisankar, Kumar, & Babu, ; Thomas & Sankar, ), spectrofluorimetric (Abdellatef, El‐Henawee, El‐Sayed, & Ayad, ; Smith, Manavalan, Kannan, & Rajendiran, ), chromatographic (Baconi, Stan, Abdul Jalil Ebrahim, Tuchila, & Balalau, ; Batool, Ahmed, & Rasheed, ; Desai, Captain, & Kamdar, ; Dhumal, Bhusari, Patra, Thareja, & Jain, ; Karunakaran, Navaneethan, & Elango, ; Kiarostami, Rouini, Mohammadian, Lavasani, & Ghazaghi, ; Ravisankar, Sridevi, & Kumari, ; Solomon, Anand, Shukla, Sivakumar, & Venkatnarayanan, ), electrochemical (Chitravathi & Munichandraiah, ; Deiminiat, Rounaghi, & Arbab‐Zavar, ; Fakhari, Sahragard, Ahmar, & Tabani, ; Ganjali, Razavi, Faridbod, Riahi, & Norouzi, ; Madrakian, Alizadeh, Bahram, & Afkhami, ) and electrophoresis (Cunha, Ribeiro, Muñoz, & Richter, ) methods in addition to the hyphenated methods where the chromatographic separations are coupled with the detection (El‐Sayed, Mohamed, Nasser, Button, & Holt, ; Haage, Kronstrand, Carlsson, Kugelberg, & Josefsson, ; Liu, Wang, Yu, Dong, & Yue, ; Tambe, Deodhar, & Prakya, ; Tanaka, Naito, Mino, & Kawakami, ; Yilmaz & Erdem, ). Thus, the aim of the present study was to develop a highly sensitive, rapid and accurate LC–MS/MS method for simultaneous quantitation of TRM and some expected co‐formulated compounds.…”
Section: Introductionmentioning
confidence: 99%